2020
DOI: 10.1021/acsptsci.0c00048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Pulmonary Arterial Hypertension: An Overview of Current and Emerging Therapies

Abstract: Pulmonary arterial hypertension is a rare and devastating disease characterized by an abnormal chronic increase in pulmonary arterial pressure above 20 mmHg at rest, with a poor prognosis if not treated. Currently, there is not a single fully effective therapy, even though a dozen of drugs have been developed in the last decades. Pulmonary arterial hypertension is a multifactorial disease, meaning that several molecular mechanisms are implicated in its pathology. The main molecular pathways regulating the pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…ARDS suffer severe hypoxemia related to intrapulmonary right-to-left shunts, and specific pulmonary vasodilators are commonly used to shift the blood flow to properly ventilated areas [ 81 ]. Furthermore, these treatments have also an anti-inflammatory effect and a beneficial effect on endothelial homeostasis [ 82 ].…”
Section: Pulmonary Hypertension: a Paradigm Of Endothelial Dysfuncmentioning
confidence: 99%
“…ARDS suffer severe hypoxemia related to intrapulmonary right-to-left shunts, and specific pulmonary vasodilators are commonly used to shift the blood flow to properly ventilated areas [ 81 ]. Furthermore, these treatments have also an anti-inflammatory effect and a beneficial effect on endothelial homeostasis [ 82 ].…”
Section: Pulmonary Hypertension: a Paradigm Of Endothelial Dysfuncmentioning
confidence: 99%
“…Over the past two decades, the development of new drugs has driven innovations in PAH therapy. However, most of these therapeutic targets are focused on vasodilation, and treatment for this disease has limitations 31 . Several previous studies have shown that patients treated with these targeted drugs have high mortality rates despite significantly improved short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therapies are divided into 4 pharmacological groups according to their mechanism of action [1,8] (Table 1):…”
Section: Current Therapeutic Weapons For Pahmentioning
confidence: 99%
“…Other vasoactive strategies such as the use of aldosterone antagonist or the angiotensin II receptor antagonist have been studied. However, despite they are generally well tolerated the appearance of some systemic severe adverse effects such as hypotension, bradycardia or hypoxemia could compromise RV function and life of PAH patients [8].…”
Section: Drugs Aiming To Improve Vascular Functionmentioning
confidence: 99%